Mako Single Stage Sag Mill Comminution Circuit Design, Commissioning and Ramp-Up - P. Hudson; P. Scinto (Canadian Institute of Mining, Metallurgy and Petroleum, 2019)
"Modern day ore bodies are becoming increasingly harder, more abrasive and lower grade. The Mako deposit is located in Senegal and consists predominantly of primary mafic and felsic lithology that are both very competent and very abrasive ores (Axb < 30, BWi >20 and Ai >1.0). The deposit was initially discovery in 2010 and the Toro Gold management team fast tracked the Mako Project through development and into production to achieve its first gold pour in January 2018. The comminution circuit comprises primary crushing single stage SAG milling with recycle crusher (1oCR SS-SAC). The mill reached design throughput and grind size seven weeks after first ore. The Mako project marks another successful international application of single stage milling, which represents a simple and easy to operate comminution circuit for small-to-mid size projects with a low capital cost. This paper describes the ore interpretation, comminution modelling, grinding circuit selection and design, as well as an overview of the commissioning and ramp-up of the mill.INTRODUCTION The Mako Gold Project is operated by Toro Gold Ltd., which holds a 90% interest in the project. The project is located in south-eastern Senegal in the Kedougou region, close to the Gambia river and township of Mako. The Mako deposit lies in the “Kenieba Window” of eastern Senegal and western Mali, which hosts a number of gold mining operations and development projects. The Mako Gold Project has an estimated life of 8 years with overall recoverable gold estimated at 924 koz. The process plant is designed to treat 1.8Mt/a of ore and produce 128 – 143 koz of gold per annum. Lycopodium Minerals Pty Ltd (Lycopodium) was appointed to provide feasibility studies and EPCM services for the greenfield project. Forming part of consultancy services provided by Lycopodium, Orway Mineral Consultants (OMC), a subsidiary of Lycopodium, was involved in the design, commissioning, ramp up and ongoing post commissioning support of the comminution circuit."